2021
DOI: 10.22541/au.162135844.47483699/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cutaneous ulcers in association with sprue-like enteropathy secondary to losartan

Abstract: Angiotensin receptor antagonist associated enteropathy is becoming increasingly prevalent within the literature. We report a case of sprue-like enteropathy associated with Losartan with a unique cutaneous manifestation. Our case of Losartan associated enteropathy further suggests that sprue-like disease may be a class effect of ARBs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…Olmesartan is associated with gastrointestinal symptoms resembling sprue‐like enteropathy 77,78 . Studies have revealed that this may be indicative of a class effect of ARBs 79–81 . The mechanistic rationale for this ADR is elusive but may be related to AT 2 receptor activation by angiotensin II 79,80 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Olmesartan is associated with gastrointestinal symptoms resembling sprue‐like enteropathy 77,78 . Studies have revealed that this may be indicative of a class effect of ARBs 79–81 . The mechanistic rationale for this ADR is elusive but may be related to AT 2 receptor activation by angiotensin II 79,80 .…”
Section: Discussionmentioning
confidence: 99%
“…77,78 Studies have revealed that this may be indicative of a class effect of ARBs. [79][80][81] The mechanistic rationale for this ADR is elusive but may be related to AT 2 receptor activation by angiotensin II. 79,80 AT 1 and AT 2 receptors are expressed throughout the gastrointestinal system.…”
Section: Biologically Relevant Inhibition Of Non-at 1 Targetsmentioning
confidence: 99%